1979
DOI: 10.1161/01.res.45.3.338
|View full text |Cite
|
Sign up to set email alerts
|

Decreased myocardial contractility in papillary muscles from atherosclerotic rabbits.

Abstract: To determine the effect atherosclerosis has on myocardial contractility, we studied the contractile properties of right ventricular papillary muscles from 34 atherosclerotic and 17 control rabbits. We produced atherosclerosis by feeding for 2 to 8 months a diet of 5% lard, 5% peanut oil, 0.5% cholesterol, and 89.5% rabbit pellets. The controls received only rabbit pellets during the same time interval. Contracting isometrically 12 times per minute at 25 degrees C, muscles from the atherosclerotic rabbits devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Although previous studies have shown that diet caused depressed cardiac function depression in isolated rabbit 12 and rat 13 papillary muscle, recent data from our laboratory 15 have shown that, in agreement with other authors 7,9,11,14 , UFA diet does not alter functional performance. On the other hand, there are few reports on the relationship between SFA rich diets and cardiac function.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although previous studies have shown that diet caused depressed cardiac function depression in isolated rabbit 12 and rat 13 papillary muscle, recent data from our laboratory 15 have shown that, in agreement with other authors 7,9,11,14 , UFA diet does not alter functional performance. On the other hand, there are few reports on the relationship between SFA rich diets and cardiac function.…”
Section: Introductionsupporting
confidence: 89%
“…Although literature shows that UFA rich diets cause morphometabolic alterations [6][7][8][9][10] , information is contradictory with respect to their effects on myocardium mechanical function 7,9,[11][12][13][14][15] . Although previous studies have shown that diet caused depressed cardiac function depression in isolated rabbit 12 and rat 13 papillary muscle, recent data from our laboratory 15 have shown that, in agreement with other authors 7,9,11,14 , UFA diet does not alter functional performance.…”
Section: Introductionmentioning
confidence: 99%
“…11 The myocardial CVI, proven to be heart rate and load independent, could be considered as an index of intrinsic myocardial contractility. 14,33 According to the elastic modules model 13 and the microscopic elastic wave theory, 16 the size and interdistance of scatters (myocytes), the acoustic impedance mismatching between the myocytes' intracellular contents and the extracellular collagen networks, as well as the ultrasonic insonification angle, 34 determine the acoustic contrast responsible for the scattering and generate the CVI.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Using chimeric mice created from Cx43-deficient stem cells and blastocysts, Gutstein et al 10 have demonstrated that spatially heterogeneous Cx43 downregulation is indeed linked to disturbances in electromechanical function in terms of both irregular epicardial conduction patterns and contractile dysfunction. 10 Dietary hypercholesterolemia has been also shown to induce contractile dysfunction independent of vascular disease, characterized by a decrease in the maximum rate of shortening and relaxation in a papillary muscle preparation, 11 although this finding has not been confirmed in isolated intact hearts. 12 Ultrasonic tissue characterization (UTC) with cardiac cycle-dependent variation of integrated backscatters (CVI) has been shown to be representation of intrinsic myocardial contractility and a potential indicator of early systolic dysfunction.…”
mentioning
confidence: 99%
“…Some investigators have not detected shortening changes in isolated rat hearts (17) or left ventricle (LV) papillary muscle (1,18), while others have detected depressed mechanical function in isolated rabbit (19) and rat (20) LV papillary muscles.…”
Section: Introductionmentioning
confidence: 99%